Development of A Mixed-Materials-Based Three-Dimensional Diorama Learning Media for The Sci-ence Subject on The Metamorphosis of Living Things for Third-Grade Students at SDN Andungsari III - Madinatul Hasanah; Ribut Prastiwi Sriwijayanti; Shofia Hattarina (International Journal of Educational Evaluation and Policy Analysis, 2026)
This study aims to develop a 3-Dimensional Diorama Learning Medium based on mixed materials for the Science subject of Metamorphosis of Living Creatures for third-grade students at Andungsari III Elementary School. The identified problem is that students have difficulty imagining the metamorphosis process through images and text. Furthermore, students may have never seen or directly observed the natural metamorphosis process. Therefore, this study aims to develop engaging learning media to increase student interest and understanding. This study employed the Research and Development (R&D) method using the ADDIE model, which consists of five stages: (1) Analysis of the problem and learning media needs; (2) Design, in the form of storyboard design; (3) Development of a 3-dimensional diorama product using mixed materials; (4) Implementation through trials with third-grade students at Andungsari III Elementary School; and (5) Evaluation based on validator feedback to assess the media validity. The results showed that the mixed-materials-based 3-dimensional diorama received a score of 88.46% from media experts, 93.18% from material experts, and 87.50% from classroom teachers, all of which were considered very appropriate. The student response questionnaire received a score of 90.67%, indicating that this medium was highly effective. Student trials showed an increase in material comprehension, with an average pretest score of 76.67 and a posttest score of 91.33. Based on these results, it can be concluded that the mixed-materials-based 3-dimensional diorama effectively improves student comprehension and motivation and is suitable for use as an innovative learning medium in science subjects in elementary schools.